Predictors of neonatal mortality among neonates admitted to the neonatal intensive care unit at Hawassa University Comprehensive Specialized Hospital, Sidama regional state, Ethiopia - Kefyalew Taye; Yenew Kebede; Desalegn Tsegaw; Worku Ketema (BMC, 2024)
Abstract Background Despite promising efforts, substantial deaths occurred during the neonatal period. According to estimates from the World Health Organization (WHO), Ethiopia is among the top 10 nations with the highest number of neonatal deaths in 2020 alone. This staggering amount makes it difficult to achieve the SDG (Sustainable Development Goals) target that calls for all nations to work hard to meet a neonatal mortality rate target of ≤ 12 deaths per 1,000 live births by 2030. We evaluated neonatal mortality and it's contributing factors among newborns admitted to the Neonatal Intensive Care Unit (NICU) at Hawassa University Comprehensive Specialized Hospital (HUCSH). Methods A hospital-based retrospective cross-sectional study on neonates admitted to the NICU from May 2021 to April 2022 was carried out at Hawassa University Comprehensive Specialized Hospital. From the admitted 1044 cases over the study period, 225 babies were sampled using a systematic random sampling procedure. The relationship between variables was determined using bivariate and multivariable analyses, and statistically significant relations were indicated at p-values less than 0.05. Results The magnitude of neonatal death was 14.2% (95% CI: 0.099-0.195). The most common causes of neonatal death were prematurity 14 (43.8%), sepsis 9 (28.1%), Perinatal asphyxia 6 (18.8%), and congenital malformations 3 (9.4%). The overall neonatal mortality rate was 28 per 1000 neonate days. Neonates who had birth asphyxia were 7.28 times more probable (AOR = 7.28; 95% CI: 2.367, 9.02) to die. Newborns who encountered infection within the NICU were 8.17 times more likely (AOR = 8.17; 95% CI: 1.84, 36.23) to die. Conclusion The prevalence of newborn death is excessively high. The most common causes of mortality identified were prematurity, sepsis, perinatal asphyxia and congenital anomalies. To avert these causes, we demand that antenatal care services be implemented appropriately, delivery care quality be improved, and appropriate neonatal care and treatment be made available.